2021
DOI: 10.12688/f1000research.54556.1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid neurofilament light levels in CLN2 disease patients treated with enzyme replacement therapy normalise after two years on treatment

Abstract: Classic late infantile neuronal ceroid lipofuscinosis (CLN2 disease) is caused by a deficiency of tripeptidyl-peptidase-1. In 2017, the first CLN2 enzyme replacement therapy (ERT) cerliponase alfa (Brineura) was approved by the FDA and EMA. The CLN2 disease clinical rating scale (CLN2 CRS) was developed to monitor loss of motor function, language and vision as well as frequency of generalised tonic clonic seizures. Using CLN2 CRS in an open label clinical trial it was shown that Brineura slowed down the progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Antisense‐mediated silencing of huntingtin did not translate into any discernible clinical benefit and CSF NfL did not normalize (in fact, it increased in the high‐dose group, potentially pinpointing a side effect) 51 . It has become clear that NfL might be a very slow biomarker in some conditions; it took 2 to 3 years for CSF NfL concentration to decline in children with enzyme replacement therapy against neuronal ceroid lipofuscinosis 52 . In anti‐Aβ antibody trials, attenuated increases of CSF NfL have been reported, 53,54 which may indicate a positive effect on neurodegeneration by the treatment, although longer and larger studies are needed.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Antisense‐mediated silencing of huntingtin did not translate into any discernible clinical benefit and CSF NfL did not normalize (in fact, it increased in the high‐dose group, potentially pinpointing a side effect) 51 . It has become clear that NfL might be a very slow biomarker in some conditions; it took 2 to 3 years for CSF NfL concentration to decline in children with enzyme replacement therapy against neuronal ceroid lipofuscinosis 52 . In anti‐Aβ antibody trials, attenuated increases of CSF NfL have been reported, 53,54 which may indicate a positive effect on neurodegeneration by the treatment, although longer and larger studies are needed.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…However, a recent study developed guidelines that significantly reduced the risk of these adverse events. 137 , 148 Given these recent advances in ERT for CNS LSDs, ERT could be an important component of their treatment in the future.…”
Section: Kd: Preclinical Investigative Therapiesmentioning
confidence: 99%